A new SO2 retrieval algorithm using total ozone mapping spectrometer radiance and its applications - Ahn, Myoung-hwan (ProQuest Dissertations & Theses Global, 1997)
"Major volcanic eruptions provide excellent opportunities to understand atmospheric processes by comparison of the theoretical atmospheric responses to the observed ones. Two recent major volcanic eruptions, the El Chichon and Mt. Pinatubo volcanoes, have attracted great attention. However, there are still many unanswered interesting questions, especially during the early stages of the volcanic eruption, mainly due to the lack of observational data. A new algorithm that retrieves column amounts of SO \sb2 and O \sb3, and aerosol signal from the radiances measured by TOMS (Total Ozone Mapping Spectrometer) has been developed. The new algorithm uses a two dimensional look-up table approach that utilizes the differential absorption of SO \sb2 in the TOMS wavelength channels. To increase the retrieval accuracy, new sets of pair wavelengths are chosen. An extensive error analysis shows that the aerosol is the most significant error source followed by uncertainties in the absorption cross sections of SO \sb2 and O \sb3. The aerosol signal in the measured radiance is corrected using the characteristics of the radiance residuals. The retrieval error due to the uncertainties in the aerosol parameters is studied. The overall error in the retrieved SO \sb2 and O \sb3 is better than 10%. The new algorithm is applied to the stratospheric volcanic cloud for the first 40 days after the eruption of the El Chichon and Mt. Pinatubo volcanoes. The volcanic dust cloud and the gaseous cloud move in different directions for the El Chichon volcano, but in the same direction for the Mt. Pinatubo volcano. The initial emission of sulfur is in the form of SO \sb2 for the Mt. Pinatubo, but the amount of SO \sb2 for El Chichon increases for the first four days, indicating that the initial sulfur is in the form of hydrogen sulfide. The total SO \sb2 masses injected by the El Chichon and Mt. Pinatubo volcanoes are about 6 Mt and 14 Mt, respectively. The chemical lifetime of gas species within the volcanic cloud, undergoing dynamical mixing and chemical conversion, can be estimated from the total mass change with time. The estimated chemical lifetime of sulfur dioxide is the same for both eruptions, about 39 days. The initial clouds for both eruptions contain little ozone, indicating the tropospheric origin of gases within the cloud. The ozone within the volcanic cloud approaches the ambient value in about four to five days, with the rate for Mt. Pinatubo being faster than for El Chichon. The reason for the fast recovery of O \sb3 is not clear yet, although it might be due to the catalytic production of O \sb3 by SO \sb2 photolysis."--Abstract.